Strategy of Tourist Village Development in Nongkosawit Sub-District, Gunungpati District, Semarang City - Eni Kusrini (Economics Development Analysis Journal, 2017)
Tourist village was formed in order to increase the tourist visits and also to improve the economy of the rural society. However, some of the tourist villages have not still given the expected results yet, one of which is the tourist village in Nongkosawit Sub-District. The aim of this research is to identify the potentiality of Nongkosawit Tourist Village that is then clarified into four aspects those are Strength, Weakness, Opportunity, and Threat. Primary data is used in this research and secondary data is also used as the supporting data. This research uses the method of quantitative descriptive and the analytic tool of SWOT. The result of SWOT shows that the proper strategy for the development of Nongkosawit Tourist Village is to minimize the internal problems in order to give benefit such as seizing better market opportunities or making new products. Suggestion that can be given through this research is that the manager of tourist village should improve the internal problems by conducting the management reconstruction and performing market segment sharpening. The manager and the communities must cooperate by supporting the development of their tourist villages so that the impact of tourist village establishment can give benefits for everyone.